Innovation Management Class in Overcoming Academic Burnout in PAI Lessons at SMAN 2 Palangka Raya - Aida, Nor; Ahmadi, Ahmadi; Surawan, Surawan (Jayapangus Press, 2025)
Success in the learning process is greatly influenced by a conducive learning atmosphere and student motivation. However, academic burnout is often an obstacle that hinders students in learning. Therefore, the application of innovation management class is very important to overcome academic burnout and support the success of the learning process. This study aims to explore the application of innovation management class as a solution in overcoming academic burnout in PAI lessons at SMAN 2 Palangka Raya. The method used is qualitative with a phenomenological approach. Data collection techniques were conducted through observation, interviews and documentation, and data validation techniques using source triangulation. The results of this study indicate that the application of innovation management class conducted by teachers in overcoming academic burnout of (83.09%) is included in the category of very effective. This is evident through a varied approach, varied methods, digital media integration, social interaction, providing rewards and motivation and carrying out technology-based evaluations that teachers apply through the stages of planning, implementation, and evaluation can increase student motivation and generate student interest in participating in learning activities. With an engaging approach to classroom management, students become more active participants and feel happy in the learning process. This research suggests that innovations in classroom management are very effective in creating a conducive learning atmosphere and successfully overcoming the challenges faced by students.